PERAN KEPERCAYAAN TAMU DALAM MEMEDIASI PENGARUH KEPUASAN KONSUMEN TERHADAP LOYALITAS PELANGGAN HOTEL TAMAN AGUNG - Affandi, Eka Yunianta; Sulistyawati, Eka (E-Jurnal Manajemen, 2015)
Consumer satisfaction is feeling happy someone to a product. Customer satisfaction that is felt can cause trust in a particular product or service. To improve customer loyalty should be focused on customer satisfaction. The impact of positive experiences experienced by consumers will establish a trus, which will lead to an increase in customer loyalty. The purpose of this study was to determine the effect of customer satisfaction on customer loyalty mediated guest confidence. This research was conducted at the Great Park Hotel in Sanur Bali. The sample many is 108 consumes respondents. The data analysis technique used is the path analysis and Sobel test. The results of this study show that customer satisfaction has positive and significant effect on Customer Loyalty and Guest Trust. Guest trust and a significant positive effect on customer loyalty and trust Guest Role significantly mediate the effect of customer satisfaction on customer loyalty.
Keywords: Consumer Satisfaction, Guest Trust, Customer Loyalty